PP.13 Previous Caesarean Delivery and the Risk of Unexplained Stillbirth: Analysis of 128, 585 Second Pregnancies in Scotland, 1999–2008. (26th April 2013) - Moraitis, AA; Smith, GC
Abstract : Background: A previous study (Lancet 2003; 362:1779–84) reported an increased risk of unexplained stillbirth in women with previous caesarean delivery among women having second births in Scotland, 1992–1998. Subsequent studies have yielded heterogeneous results but have employed data, analytic approaches and interpretation of variable quality. Methods/Results: We replicated our previous methods and analysed 128, 585 eligible singleton second births between 1999 and 2008. There were 88 stillbirths among 23, 688 women with a previous caesarean (2.33 per 10, 000 women per week) and 288 stillbirths in 104, 897 women who previously delivered vaginally (1.67 per 10, 000 women per week, P = 0.002). When analysed by cause, women with a previous caesarean had an increased risk (hazard ratio [95%CI] P) of unexplained stillbirth (1.47 [1.12–1.94] P = 0.006) and the excess risk was apparent from 34 weeks onwards (1.75 [1.23–2.49] P = 0.002). When the analysis was confined to 96, 988 women with linked records from the first and second pregnancy (confirming exact mode of previous delivery) the association was stronger (2.12 [1.55–2.88] P < 0.001). Adjustment for maternal characteristics and first pregnancy complications had a minimal effect (1.97 [1.43–2.72] P < 0.001). The association was similar weather the previous caesarean was performed prior to labour (2.1[1.24–3.80] p = 0.007) or during labour (2.50 [1.53–4.08] p < 0.001) and when the analysis was confined to previous term births (2.35 [1.50–3.53] p < 0.001). Conclusion: We confirm that previous finding that previous caesarean delivery is a risk factor for unexplained stillbirth. The association is independent of maternal characteristics, obstetric outcome or the indication for the caesarean delivery.